Syntrophic oxidation of butyrate and ethanol - Schmidt, Alexander (My University, 2014)
Syntrophic bacteria live at the thermodynamic limit of growth. The biochemistry of those secondary fermenters is not fully understood yet. In this thesis, two model systems of syntrophic organisms growing on two difficult to degrade substrates were investigated: Syntrophomonas wolfei in coculture with Methanospirillum hungatei converting butyrate to acetate and methane and Pelobacter carbinolicus or P. acetylenicus in coculture with M. hungatei fermenting ethanol to acetate and methane.
All prominent membrane-bound and soluble proteins expressed in S. wolfei specifically during syntrophic growth with butyrate were examined by 1D- and 2D-PAGE. A membrane-bound, externally oriented formate dehydrogenase complex was expressed at high level. Soluble hydrogenases were expressed at high levels specifically during growth with the pure-culture substrate crotonate. The results were confirmed by native PAGE, by formate dehydrogenase and hydrogenase-activity staining, and by analysis of formate dehydrogenase and hydrogenase activities in intact cells and cell-free extracts. In S. wolfei, electrons derived from butyryl-CoA are hypothesized to be transferred through a membrane-bound EtfAB:quinone oxidoreductase to a menaquinone cycle and further via a b-type cytochrome to an externally oriented formate dehydrogenase. Hence, an ATP hydrolysis-driven proton-motive force across the cytoplasmatic membrane would provide the energy input for the electron potential shift necessary for formate formation.
The membrane-associated and cytoplasmic enzymes of P. carbinolicus and partially also P. acetylenicus were investigated with 1D- and 2D-PAGE, enzyme tests and cultivation experiments as well. In the cytoplasmic fraction of ethanol-grown P. carbinolicus cells, acetaldehyde was oxidized mainly to acetyl-CoA. Hence, substrate-level phosphorylation appeared to be the dominant mode of energy conservation. Additionally, a ferredoxin-dependent, non-acetylating acetaldehyde dehydrogenase activity could be detected. Comparative 2D-PAGE revealed enhanced expression of tungsten-dependent acetaldehyde:ferredoxin oxidoreductases and formate dehydrogenase. Proteomics allowed the detection of an Rnf subunit once and several putatively Na+-dependent ATP synthase subunits in membrane preparations. Protein purification allowed the enrichment and identification of P. carbinolicus ferredoxin Pcar_2544 which had 44% sequence identity to Clostridium pasteurianum ferredoxin. Comproportionating hydrogenases and formate dehydrogenase were expressed constitutively and are probably involved in interspecies electron transfer. The hydrogenase activity depended on flavin mononucleotide. In ethanol-grown cocultures, the maximum hydrogen partial pressure was about 1,000 Pa (1 mM) while 2 mM formate was produced. The redox potentials of hydrogen and formate released during ethanol oxidation were calculated to be EH2 = -358 ± 12 mV and EHCOOH = -366 ± 19 mV, respectively. Both hydrogen and formate contributed to interspecies electron transfer. Both Pelobacter species could be cultivated axenically on acetaldehyde, yielding energy from its disproportionation to ethanol and acetate. The early assumption that acetaldehyde is a central intermediate in Pelobacter metabolism has now been proven biochemically.
One of the first scientists publishing (in 1916) on microbial methanogenesis from butyrate and ethanol was V. L. Omeljanskij (1867-1928). Although he was an early pioneer of methanogenesis research, his lifework was never presented to an international audience. He founded a school of thought based on his teacher’s S. N. Vinogradskij’s discoveries and theories in Russia and the USSR. Omeljanskij published the first Russian textbook on microbiology, “Principles of microbiology” (“Основы микробиологии“) in 1909. He published internationally in German, French and English, thus representing a cross-border type of scientist.
Keywords: Syntrophie, syntrophy, Sytrophomonas wolfei, Pelobacter, Ethanol, Butyrat; 570